Communication as a Panacea for Resolving Crises in Energy Industry: The Case of Ikeja Electricity Distribution Company - Ajibola, Olawale Olaniyi Emmanuel; Adeniji, Rasaki Idowu; Omiyale, Abolade David (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Communication is the process by which people exchange information through a common set of symbols. It is appropriate to describe modern society as a knowledge society, in which ideas and information enabled by engineering are highly valued and knowledge has a big impact on the development process, including engineering education. However, the key to acquisition of knowledge is communication, thus the importance of communication in any ecosystem cannot be overemphasized; it is the life upon which an institution derives its existence. Without adequate communication, goals and aspiration of an organization will be difficult to achieve. The purpose of this research study which targets Ikeja Electricity Distribution Company (IKEDC) is to re-emphasize the importance of communication in resolving crisis, most especially in the energy sector where every effort made by the federal government of Nigeria to ensuring smooth delivery of uninterrupted supply of electricity for the consumption of hoi polloi to adequately facilitate engineering education. The results revealed that horizontal communication is an effective tool for crisis resolution. It also revealed that employees of IKEDC do not receive sufficient horizontal information to perform their duties successfully, and upward communication has not helped in resolving the energy issues. The study’s objective is to ensure a steady power supply for the efficient operation of engineering education by encouraging the best possible use of IKEDC’s current infrastructures through horizontal communication.